2018
DOI: 10.1007/s00411-018-0751-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of neutron organ and effective dose coefficients for PIMAL stylized phantom in bent postures in standard irradiation geometries

Abstract: Neutron dose coefficients for standard irradiation geometries have been reported in International Commission on Radiological Protection (ICRP) Publication 116 for the ICRP Publication 110 adult reference phantoms. In the present work, organ and effective dose coefficients have been calculated for a receptor in both upright and articulated (bent) postures representing more realistic working postures exposed to a mono-energetic neutron radiation field. This work builds upon prior work by Dewji and co-workers com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 13 publications
1
12
0
Order By: Relevance
“…In general, the effective dose conversion coefficients obtained in the current study coincide with those reported by Bales et al (2018) with the same PIMAL phantom. However, compared to the results provided in (Bales et al, 2018) a much better agree ment with the dose conversion coefficients published by ICRP (ICRP, 2010) was obtained in the current study for neutron energy lager than 5 MeV.…”
Section: Organ Absorbed Dose Conversion Coefficient With the Pimal Ph...supporting
confidence: 89%
See 3 more Smart Citations
“…In general, the effective dose conversion coefficients obtained in the current study coincide with those reported by Bales et al (2018) with the same PIMAL phantom. However, compared to the results provided in (Bales et al, 2018) a much better agree ment with the dose conversion coefficients published by ICRP (ICRP, 2010) was obtained in the current study for neutron energy lager than 5 MeV.…”
Section: Organ Absorbed Dose Conversion Coefficient With the Pimal Ph...supporting
confidence: 89%
“…7(a) (e) compare for the standard irradiation geometries AP, PA, LLAT, RLAT and ISO, the effective dose conver sion coefficients obtained by the PIMAL phantom in vertical upright posture with the respective coefficients provided by ICRP obtained by the ICRP/ICRU reference voxel phantom as given in the publication 116 (ICRP, 2010). Also included in the subfigures for the AP, PA, LLAT and RLAT geometries are the dose conversion coefficients reported by Bales et al (2018) with the same PIMAL phantom as in the current study. Noted that for the ISO irradiation geometry no data was available in the publication of Bales et al (2018).…”
Section: Organ Absorbed Dose Conversion Coefficient With the Pimal Ph...mentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, several investigators have developed NURBS/polygonal mesh (PM)-based hybrid phantom that can address the limitations of the voxel phantom and be deformed in various postures. 12,[15][16][17][18] Based on this, the deformed hybrid phantom has been modeled with various ages and shapes. In addition, a program to convert the hybrid phantom to DICOM was developed for the purpose of clinical application.…”
Section: Introductionmentioning
confidence: 99%